Manipulating the water–air interface to drive protein assembly for functional silk-like fibroin fibre production - Rafael O. Moreno-Tortolero; Juliusz Michalski; Eleanor Wells; Flora Gibb; Nick Skaer; Robert Walker; Louise Serpell; Chris Holland; Sean A. Davis (Communications Materials)
Abstract Silk’s remarkable properties arise from its hierarchical structure, formed through natural transformation from an aqueous solution to a solid fibre driven by pH and flow stress under low-energy conditions. In contrast, artificial silk fabrication typically relies on extrusion-based methods using coagulating baths and unnatural solvents, limiting true biomimetic replication. Here, we find that native-like silk fibroin forms viscoelastic films at the air-water interface. Utilizing this, we demonstrate a mild, all-aqueous method to seamlessly pull silk-like fibres with co-aligned nanofibrillar bundles. The fiber structure transitioned from hexagonally packed β-solenoid units at low pulling speeds to β-sheet-rich structures at higher speeds. Fibers pulled near physiological speeds (26.3 mm s-¹) exhibited optimal mechanical properties, with an elastic modulus of 8 ± 1 GPa and toughness of 8 ± 5 MJ m-³, comparable to natural silk. This platform also enables embedding nanoparticles and biologics, offering broad applications in sensors, biocatalysis, and tissue engineering, expanding the potential of silk-based composite materials.